2023
DOI: 10.1556/032.2023.00009
|View full text |Cite
|
Sign up to set email alerts
|

Import intensities of final demand components and their implications for economic openness: The case of the Czech Republic

Abstract: The article deals with the estimation of import intensities of exports, final consumption expenditures and gross fixed capital formation. It uses the input-output methodology of computing direct and indirect imports to the final demand components, which compares with regression estimates. Unlike the widely used turnover approach, the results contribute fundamentally to knowledge about the genuine openness of the Czech economy with regard to how much value-added is exported. In 2015, the highest import intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Thus, it is found that Export have a positive impact on economic growth, results also found by other authors [38,39]. Through the GLV(4) model, it is found that the increase in Export accelerates not only economic growth, but also the ability to Import and make Investment, results also found by other studies [34,41,49].…”
Section: Comparison Between the Types Of Relationships Identified Wit...supporting
confidence: 77%
See 2 more Smart Citations
“…Thus, it is found that Export have a positive impact on economic growth, results also found by other authors [38,39]. Through the GLV(4) model, it is found that the increase in Export accelerates not only economic growth, but also the ability to Import and make Investment, results also found by other studies [34,41,49].…”
Section: Comparison Between the Types Of Relationships Identified Wit...supporting
confidence: 77%
“…For the period 2011-2022 there is a relationship of type Predator-Prey, while for 2005-2022 the relationship is of type Competition. It is found, as in other studies, that in the long term the coexistence between Import and Investment is also influenced by the evolution of Export and economic growth [49].…”
supporting
confidence: 82%
See 1 more Smart Citation